Enhancing Students’ Drama Performance: A Process Approach - Syamsul Bahri; Meisuri Meisuri (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2020)
This research aims at describing and developing website based authentic assessment model on drama course in English literature study program. The research data comes from descriptive information of the experts or validator along with the suggestion from the students as the product user through the PBL activity combined with the observation and recording with video tape. Data analysis is done by using rubric measure: a) the information completeness which is applied on the work sheets. b) the information comprehensiveness which is included in the paragraph written by the students. The overall of the flow diagram are :  Preparation: choosing the research based article which is relevant with the course; preparing worksheet and observation sheet.  Implementation: the students read the research based article and fill in the worksheet. . Observation: filling in the observation sheet and writing anecdotal record. Reflection: analyzing the observation sheet and measurement rubric. With the implementation of authentic assessment toward the students who participate in the drama appreciation course. The obtained results show significant increase in their competence through the 6 kinds of task which contain website based authentic assessment on the stage of manipulating expression, scripting, dialogue reading, pre performing and stage performance.